IMPACT OF BRAND AUTHENTICITY AND SOCIAL MEDIA ON CUSTOMER BEHAVIOUR. A CASE OF PAKISTAN’S FOOD MANUFACTURING INDUSTRY - Dr. Muhammad Ghazanfar Abbas; Dr. Javed Miraj; Parvez Ahmed Shaikh; Nasir Ali (International Journal of Contemporary Issues in Social Sciences, 2023)
The main aim of the study is to understand the concept of authenticity and the integration of social media in enhancing the brand authenticity. Authenticity is the main aspect of creating trust. By keeping the authenticity in a real sense, the association between the brand and the followers becomes relatively stronger The research design of the study is quantitative research which implies the use of the data in the numerical form tested through the statistical tools. The researcher has also used the positivism philosophy that is used in the research where the scientific method for obtaining the information is used. Furthermore, the quantitative approach in this study has been used as it has been indicated to be the most suitable technique when studying the relationship between the variables The results of the study indicate there is a significant association between Brand Authenticity and social media on Customer Behaviour. It further indicates that it is important for brand preference to be considered while determining the customer behaviour as it leads to effective customer brand relationship to be determined The study has provided a theoretical framework for brand authenticity and social media’s impact on it. Managerial objectives can be facilitated by this framework to develop an understanding of the importance of social media.